PENGEMBANGAN BUKU ELEKTRONIK FISIKA DASAR BERBASIS PENDEKATAN SAINTIFIK PADA MATERI FLUIDA STATIS DAN DINAMIS - Fadhillah, Nanda; Pathoni, Haerul; Alrizal , Alrizal (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aims to describe how the process of developing E-Book on Basic Physics material and to find out students' perceptions of E-Books based on scientific approaches on Static and Dynamic Fluid materials. This research design uses a research and development design with a 4D model which consists of four stages; define, design, develop, and disseminate. The data were analysed using descriptive quantitative and qualitative. From 34 respondents in the 2019 class of physics education at Jambi University, more than 50% revealed that basic physics material is difficult to understand. In the Static and Dynamic Fluid material, it has a difficulty percentage of 58%. As many as 94% of students need additional teaching materials and have never used teaching materials based on a scientific approach in the process of basic physics courses. The results of the validation by the experts of materials and media indicated that the E-Book were feasible to be tested with agree criteria. The E-Book trial shows that the overall indicator given based on student perceptions was 52 in the very good category.